Analysis of Legal Protection for Start-up Companies as Partner Companies in Venture Capital Agreements - Sudja’i; Muzakki Affandi; Muh. Bangsu (LEGAL BRIEF, 2021)
The focus of this research is to determine how investors in venture capital agreements and start-up enterprises as business partners are legally protected. This research employs an empirical-juridical qualitative method in conjunction with a descriptive analytic technique for collecting data via a literature review. The purpose of this research is to determine how investor businesses in venture capital agreements and start-up companies as business partners are legally protected. This research is also a review of the legal literature. According to the research and discussion, there have been no standards governing venture capital performance since Presidential Decree No. 9 of 2009 and Minister of Finance Decree No. 18/PMK.010/2012. The technique is predicated on the concept of contract freedom, which is realized through the submission of a contract (agreement) to the parties. The venture capital financing agreement is then implemented using a standard contract model determined in advance by the venture capital company, which frequently results in partner companies accepting only what the venture capital company offers, as the basic rules governing standard agreements in Indonesia are unavailable. These conditions create an imbalance between the parties and are frequently viewed as unfair—partner companies whose position as a weak party has not yet been adequately protected by law. which frequently results in partner companies accepting only what the venture capital company offers, as the basic rules governing standard agreements in Indonesia are unavailable. These conditions create an imbalance between the parties and are frequently viewed as unfair—partner companies whose position as a weak party has not yet been adequately protected by law which frequently results in partner companies accepting only what the venture capital company offers, as the basic rules governing standard agreements in Indonesia are unavailable. These conditions create an imbalance between the parties and are frequently viewed as unfair—partner companies whose position as a weak party has not yet been adequately protected by law.